Impact of substrate defects on the equilibrium one-dimensional island size distribution - Mirabella, D. A. (2011)
As long as only first-neighbour interactions are considered, equilibrium island size distributions of monoatomic islands in one dimension follow an exponential law regardless of the strength and the repulsive or attractive character of the adsorbate–adsorbate interactions. However, one- dimensional atomic wires obtained via nucleation at the step edges have a monomodal island size distribution. In this paper, we present a simple one- dimensional Monte Carlo model that shows how the monomodal distribution observed experimentally can be obtained by including surface defects that only suppress the interaction between two successive adsorbates.